OPTIMIZATION OF ADENOVIRUS VECTOR-BASED COVID-19 VACCINE CANDIDATE PRODUCTION WITH LACO AND INTRON MODIFICATION - Rahma Bassalamah, Annisa
Adenovirus is a commonly used viral vector-based vaccine platform to deliver antigen gene. Adenoviral production may be suppressed by antigen expression in the packaging cells hence it needs to be regulated for an optimal production. In the previous study, recombinant adenovirus genome carrying SARS-CoV-2 spike gene with lac operator (lacO) and intron sequence has been constructed. This study aimed to optimize production of adenoviral vector with lacO and intron. Optimation was performed on the producer cell lines, the number of infections, and the incubation time for production. Optimal conditions were determined based on the highest titer of adenovirus vectors produced. Recombinant adenovirus genome was transfected to AD293 and HEK293 cells and the adenovirus vectors was harvested after 10 days of incubation as primary stock. The adenovirus stock was then infected and harvested from cells repeatedly for adenovirus propagation. For each round of propagation, viral titers were determined, and adenovirus vector was characterized through polymerase chain reaction (PCR) to confirm the presence of hexon, spike, as well as lacO and intron fragment. Production of recombinant adenovirus vectors, AdV-LacO-S and AdV-LacO-Intron-S, in AD293 showed higher viral titer than in HEK293. Adenovirus production at multiplicity of infection (MOI) 1, 2, and 5 for 4 days incubation showed equivalent titers in AD293, but increased in HEK293. Extending the incubation time to 9 days in both cells showed no increase in viral titer, except for AdV-LacO-Intron-S production in HEK293 at MOI 1 which reached highest titer at 7 days of incubation. AdV-LacOS was optimally produced in both adherent cells at MOI 1 for 5 days incubation. AdV-LacO-Intron-S titer shown in this study served as evidence that the expression of spike transgene in packaging cells could inhibit adenovirus production. Increased viral titers proportional to MOI in HEK293 cells can serve as a reference for the next production optimization in suspension cells.